TINGKATKAN EFISIENSI DAN AKURASI: INOVASI PELATIHAN APARATUR NEGERI DALAM PENCATATAN DATA REGISTRASI PENDUDUK - Murwani, Prapti; Titaley, Elsina; Manuputty, Pieter Hendra; Darakay, Jurnie; Loppies, Lussi R. (CV. Kalimasada Group, 2024)
The improvement of efficiency and accuracy in recording population registration data is a primary challenge for local governments, particularly in Seith Pulau Ambon. This article documents community service efforts aimed at enhancing the quality of public services through the innovation of civil servant training. The approach involves a training strategy focused on strengthening the technical and managerial skills of civil servants in recording population data. Through interactive and practically oriented training methods, this article reviews the positive impact of this innovation on improving the efficiency of the data recording process. The systematic training includes a profound understanding of registration procedures, the utilization of cutting-edge technology, and the enhancement of coordination among civil servants. As a result, civil servants in Seith Pulau Ambon can provide population registration services with higher accuracy and more efficient timing. This article not only provides detailed insights into the implemented training strategies but also evaluates its positive impact on the improvement of public service quality. By implementing this training innovation, it is expected to serve as a model for other regions facing similar challenges and make a tangible contribution to enhancing public administration systems at the local level.